Cooperative Patterns in the Egyptian Colloquial Arabic - Siti Aminah; Amir Ma'ruf (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article described the cooperative patterns formed in the Egyptian speech community using Egyptian Colloquial Arabic (ECA). The data were taken by using participatory observation method through the recording and note-taking techniques. By employing Grice’s theory of cooperative principles and maxims, this study suggested that speech events in Egyptian society had a variety of cooperative patterns. The varied patterns could be seen in the negotiation processes to reach an agreement. Therefore, the negotiations required a lot of energy and time.